Adaptability and stability of corn inbred lines regarding resistance to gray leaf spot and northern leaf blight - Saito, Belisa Cristina [UNESP]; Silva, Leonardo Queiroz [UNESP]; Costa Andrade, Joao Antonio da [UNESP]; Goodman, Major M. (Brazilian Soc Plant Breeding, 2018)
The objectives of this study were to identify resistant and susceptible corn inbred lines based on their stability and adaptability for resistance to disease symptoms of gray leaf spot and northern leaf blight, suggest resistant inbred lines aimed at producing synthetics, and identify the sowing dates with higher occurrence of diseases to use these dates for identification of genetic resistance. We evaluated 41 corn inbred lines in randomized block designs with three replications and 11 sowing dates. Evaluations were performed 30 days after silking. Stability and adaptability analyses were performed by the regression method. The highest severities of disease occurred in sowing from June to September. On average, all the inbred lines were classified as resistant; however, considering adaptability and stability, five inbred lines were found suitable to produce dent synthetics resistant to both diseases. For flint synthetics resistant to both diseases, inbred lines IVF1-7,IVF1-10, 2F, 9F, and 10F are most suitable.
Keywords: Leaf diseases; disease resistance; synthetic